MDA Based Multiplatform Mobile Application Modeling with Platform Compliant User Interfaces - Vranić, Valentino; Staraček, Ľuboš (INFOCOMP Journal of Computer Science, 2014)
<span style="color: #484848; font-family: Tahoma, Arial, sans-serif; font-size: 11px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 16.5px; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; -webkit-text-stroke-width: 0px; display: inline !important; float: none; background-color: #ffffff;">Applications for mobile devices (mobile applications) represent a specific segment of the software market in which development of applications for multiple platforms is far more articulated issue than in applications intended for common computers. <span style="margin: 0px; padding: 0px; color: #484848; font-family: Tahoma, Arial, sans-serif; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; -webkit-text-stroke-width: 0px; font-size: 12.1599998474121px; line-height: 1.3em; background-color: #ffffff;">While multiplatform mobile application development tools, <span style="margin: 0px; padding: 0px; color: #484848; font-family: Tahoma, Arial, sans-serif; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; -webkit-text-stroke-width: 0px; font-size: 12.1599998474121px; line-height: 1.3em; background-color: #ffffff;">such as Marmalade, MoSync or Xamarin, <span style="margin: 0px; padding: 0px; color: #484848; font-family: Tahoma, Arial, sans-serif; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; -webkit-text-stroke-width: 0px; font-size: 12.1599998474121px; line-height: 1.3em; background-color: #ffffff;">generate quite usable (software) platform specific code out of its general representation developed upon something that might be considered as a superplatform, <span style="margin: 0px; padding: 0px; color: #484848; font-family: Tahoma, Arial, sans-serif; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; -webkit-text-stroke-width: 0px; font-size: 12.1599998474121px; line-height: 1.3em; background-color: #ffffff;">the user interface exhibits peculiarities that have to be addressed manually. <span style="margin: 0px; padding: 0px; color: #484848; font-family: Tahoma, Arial, sans-serif; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; -webkit-text-stroke-width: 0px; font-size: 12.1599998474121px; line-height: 1.3em; background-color: #ffffff;">Otherwise, the user interface will probably fail to meet the given platform compliance criteria that may result in worsening user acceptance of the application or even in not being accepted to the application marketplace at all. <span style="margin: 0px; padding: 0px; color: #484848; font-family: Tahoma, Arial, sans-serif; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; -webkit-text-stroke-width: 0px; font-size: 12.1599998474121px; line-height: 1.3em; background-color: #ffffff;">In this paper, an approach to design multiplatform mobile application at model level that employs OMG’s MDA (Model Driven Architecture) to generate platform compliant user interfaces while still taking advantage of multiplatform tools to develop application logic is proposed. <span style="margin: 0px; padding: 0px; color: #484848; font-family: Tahoma, Arial, sans-serif; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; -webkit-text-stroke-width: 0px; font-size: 12.1599998474121px; line-height: 1.3em; background-color: #ffffff;">Navigation in mobile application user interfaces is modeled using UML state machine diagrams. <span style="margin: 0px; padding: 0px; color: #484848; font-family: Tahoma, Arial, sans-serif; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; -webkit-text-stroke-width: 0px; font-size: 12.1599998474121px; line-height: 1.3em; background-color: #ffffff;">A model-to-model transformation for the Android platform has been created and applied to a real application model.